THE THREATS AND COUNTER TERRORISM OF ARMED CRIMINAL GROUP IN PAPUA (THREATS AND HANDLING OF TERRORISM CRIMES AGAINST ARMED CRIMINAL GROUPS IN PAPUA) - I Made Pasek Saradahtam B; Rio Adhikara; Wildhan Indra P (Bajang Institute, 2021)
Recent geostrategic dynamics and Indonesia's national security are still tinged with threats, both internal and external, in the form of acts of terrorism. Therefore, it is necessary to anticipate efforts to secure Indonesia's geostrategy in global and regional political dynamics which can be used as input and consideration in the life of the nation and state in order to protect Indonesia's national interests, so that the struggle process realizes national goals in order to achieve the ideals. Indonesia's national affairs can take place safely and smoothly. This study uses geostrategic and legitimacy concepts that reflect the response of the Indonesian National Police in tackling the threat of terrorism in the form of policies or strategies for strict law enforcement and prevention efforts in the form of counter-radicalization and deradicalization as a form of community policing in combating terrorism by upholding high value of human rights within.